D.08 ACT DMD (Ataluren Confirmatory Trial in Duchenne Muscular Dystrophy): effect of Ataluren on timed function tests (TFT) in nonsense mutation (nm) DMD. (17th June 2016) - Goemans, N; Campbell, C; McDonald, CM; Voit, T; Luo, X; Elfring, G; Kroger, H; Riebling, P; Ong, T; Spiegel, R; Peltz, SW; Bushby, K
Abstract : Background: Ataluren is the first drug to treat the underlying cause of nmDMD.Methods: ACT DMD is a Phase 3, randomized, double-blind study. Males 7-16 years with nmDMD and a screening six-minute walk distance (6MWD) ≥150 m and <80%-predicted were randomized to ataluren 40 mg/kg/day or placebo for 48 weeks. A pre-specified subgroup included patients with baseline 6MWD 300-400 m. A meta-analysis of the overall ACT DMD population and the 'ambulatory decline phase' subgroup of the Phase 2b study (those patients meeting ACT DMD entry criteria) was pre-specified in the statistical plan.Results: In the overall ACT DMD population (N=228), changes in TFTs favored ataluren over placebo: 10-meter walk/run, -1.2s (p=0.117); 4-stair climb, -1.8s (p=0.058); 4-stair descend, -1.8s (p=0.012). In the pre-specified subgroup (n=99), these differences increased to -2.1s, -3.6s, and -4.3s, respectively, and were statistically significant (p<0.01) for 4-stair climb and descend. Results are supported by the meta-analysis (N=291), which demonstrated significant differences (p<0.05) in 10-meter walk/run, 4-stair climb, 4-stair descend.Conclusions: TFT results showed a benefit for ataluren in ACT DMD, and a larger treatment effect in the pre-specified baseline 6MWD 300-400 m subgroup as well as the pre-specified meta-analysis of ACT DMD and the Phase 2b study decline subgroup. Supported By: PTC Therapeutics Inc.